milR20 negatively regulates the development of fruit bodies in Pleurotus cornucopiae - Qi, Yuhui; Huang, Chenyang; Zhao, Mengran; Wu, Xiangli; Li, Guangyu; Zhang, Yingjie; Zhang, Lijiao (Frontiers in Microbiology, 2023)
The mechanism underlying the development of fruit bodies in edible mushroom is a widely studied topic. In this study, the role of milRNAs in the development of fruit bodies of Pleurotus cornucopiae was studied by comparative analyses of the mRNAs and milRNAs at different stages of development. The genes that play a crucial role in the expression and function of milRNAs were identified and subsequently expressed and silenced at different stages of development. The total number of differentially expressed genes (DEGs) and differentially expressed milRNAs (DEMs) at different stages of development was determined to be 7,934 and 20, respectively. Comparison of the DEGs and DEMs across the different development stages revealed that DEMs and its target DEGs involved in the mitogen-activated protein kinase (MAPK) signaling pathway, protein processing in endoplasmic reticulum, endocytosis, aminoacyl-tRNA biosynthesis, RNA transport, and other metabolism pathways, which may play important roles in the development of the fruit bodies of P. cornucopiae. The function of milR20, which targeted pheromone A receptor g8971 and was involved in the MAPK signaling pathway, was further verified by overexpression and silencing in P. cornucopiae. The results demonstrated that the overexpression of milR20 reduced the growth rate of mycelia and prolonged the development of the fruit bodies, while milR20 silencing had an opposite effect. These findings indicated that milR20 plays a negative role in the development of P. cornucopiae. This study provides novel insights into the molecular mechanism underlying the development of fruit bodies in P. cornucopiae.